Classroom factors and academic performance of 4th year BS Criminology students of UM Bansalan College, Bansalan, Davao del Sur - Borlaza, Orlie R.; Alcebar, Ronell T.; Cabahug, James Paul J. (--Davao del Sur: UM Bansalan College, 2016)
This study was conducted to determine the level of classroom factors in affecting the academic performance of 4th year BS criminology students in UM Bansalan College. The researchers aim to determine the significant relationship between the level of classroom factors and academic performance of 4th year BS criminology students. This study examined the outcome of a survey conducted to the 4th year BS Crminology students of UM Bansalan College by employing a descriptive-correlation method to determine the level of classroom factors academic performance. The data analysis exposes that classroom factors gained a high status and the analysis further shows that there is no significant relationship between classroom factors and academic performance of 4th year BS Criminology students which shows that learning preference vary in every students. Results show that the level of classroom factors affecting the academic performance of 4th year BS criminology students is high. Furthermore, results show that majority of the respondents performed well academically. The researchers then highly recommend that to achieve exemplary student academic performance, the school must provide facilities that are conducive for learning, teachers must constantly use course materials to monitor the progress of class activities and at the same time use effective strategies on hot to address learning difficulties.